Composite diaphragm, preparation method thereof and battery
By using a composite coating on the lithium battery separator, the problems of slow lithium ion transfer and poor electrolyte storage capacity during the fast charging process of lithium batteries are solved, and the battery is fast charging and discharge and high cycling performance are achieved.
Patent Information
- Application Number
- CN202510294585.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-11
AI Technical Summary
The existing coated diaphragms cannot quickly transfer lithium ions during the fast charging process of lithium batteries, and the electrolyte storage capacity is poor, making it prone to shrinkage problems.
A composite separator is used, which includes a base film and a composite coating arranged on one surface of the base film. The composite coating consists of an inorganic filler and a polymer, and has a recessed portion and a protruding portion. The protruding portion and a recessed portion are alternately distributed to ensure excellent liquid storage performance and heat resistance.
It realizes the transfer of lithium ion for fast charging and discharging, improves the liquid storage capacity of the electrolyte, avoids the problem of shrinkage, and improves the circulation and safety performance of the battery.
Smart Images

Figure CN119812674A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a composite diaphragm and a preparation method thereof, and a battery. Background Art
[0002] With the development of the market, the market share of new energy vehicles has increased year by year. After the endurance problem has been basically solved, the current new energy vehicle owners are more concerned about the speed of charging. The main function of the diaphragm in the battery is to keep the positive and negative electrodes separated to prevent short circuits, while allowing the rapid transfer of ions. It is a more important component in the battery. The performance of the diaphragm will directly affect the characteristics of the battery, such as the battery's capacity, rate, cycle and other performance. Traditional coated diaphragms cannot transfer a large amount of lithium ions in a short period of time during fast (super) charging processes such as 4C of lithium batteries. In addition, the electrolyte storage capacity of traditional diaphragms is poor and they are prone to shrinkage problems.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] One object of the present invention is to provide a composite membrane to solve the technical problems of poor liquid storage performance and easy shrinkage of coated membranes in the prior art. In the composite membrane of the present invention, the composite coating can give it excellent liquid storage performance, heat resistance and structural stability.
[0005] Another object of the present invention is to provide a method for preparing a composite membrane, which is simple, easy to operate and environmentally friendly.
[0006] Another object of the present invention is to provide a battery having excellent cycle performance.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: A composite diaphragm comprises a base film and a composite coating disposed on at least one side of the base film; the composite coating comprises an inorganic filler and a polymer, the polymer being selected from a first polymer, or a first polymer and a second polymer; the composite coating comprises a concave portion and a convex portion; the convex portion comprises a plurality of parallel convex structures, the concave portion comprises a plurality of parallel concave structures, the convex structures and the concave structures are alternately distributed; the average thickness H2 of the concave portion and the average thickness H1 of the convex portion satisfy: 0.2≤H2 / H1≤0.95; the average width W2 of the concave portion and the average width W1 of the convex portion satisfy: 0.1≤W2 / W1≤6.5; the average width W1 of the convex structure is 0.8-10 mm. The first polymer comprises at least one of polyacrylate, polyurethane acrylate, styrene-butadiene rubber, polyvinyl alcohol and polyacrylamide. The second polymer comprises at least one of polyvinylidene fluoride, polymethyl methacrylate, polyamide, polyimide and polyacrylonitrile.
[0008] In some embodiments, the average thickness H1 of the convex structure is 0.5-15 μm.
[0009] In some embodiments, an average thickness H2 of the recessed portion and an average thickness H1 of the raised portion satisfy: 0.55≤H2 / H1≤0.8.
[0010] In some embodiments, the average width W2 of the recessed portion and the average width W1 of the raised portion satisfy: 1≤W2 / W1≤3.
[0011] In some embodiments, an angle θ between an extension direction of the convex structure or the concave structure and an MD direction of the base film is 0-80°.
[0012] In some embodiments, an angle θ between an extension direction of the convex structure or the concave structure and an MD direction of the base film is 60° to 80°.
[0013] In some embodiments, the width error δ1 of the convex structure in the continuous extension dimension satisfies: δ1=(W1 max -W1 min ) / W1 min ≤10%, where W1 max Indicates the maximum width of the convex structure, W1 min Indicates the minimum width of a convex structure.
[0014] In some embodiments, the width error δ2 of the concave structure in the continuous extension dimension satisfies: δ2=(W2 max -W2 min ) / W2 min ≤10%, of which W2 max represents the maximum width of the concave structure, W2 min Represents the minimum width of the concave structure.
[0015] In some embodiments, in the cross section of the composite coating, the convex structure and the concave structure are in an arc-linear sinusoidal wave configuration or a linear platform configuration.
[0016] In some embodiments, in the composite coating, the mass percentage of the inorganic filler is 67% to 97%, and the mass percentage of the second polymer is 0% to 30%.
[0017] In some embodiments, the inorganic filler includes at least one of alumina, boehmite, silica, magnesium hydroxide, barium sulfate, calcium carbonate, titanium dioxide, silicon carbide, and silicon nitride.
[0018] In some embodiments, the base film comprises PP and / or PE.
[0019] In some embodiments, the base film has a thickness of 2 to 20 μm.
[0020] The method for preparing the composite diaphragm as described above comprises the following steps: The inorganic filler, the polymer material and the solvent are mixed to obtain a mixed slurry.
[0021] The mixed slurry is coated on at least one side of the surface of the base film, and the composite diaphragm is obtained after drying.
[0022] In some embodiments, the mass ratio of the inorganic filler to the solvent is (67-97):(122-400).
[0023] A battery comprises the composite diaphragm.
[0024] Compared with the prior art, the present invention has the following beneficial effects: (1) The composite diaphragm of the present invention has a composite coating with the above-mentioned specific structure. When the composite diaphragm and the electrode are heat-set, the raised portion can effectively play the role of supporting space, and the recessed portion can effectively provide sufficient space to store electrolyte, which can provide a large amount of lithium ions for rapid charging and discharging; the continuous composite coating can effectively avoid the composite diaphragm from shrinking at high temperatures due to obvious uneven coating distribution; the composite diaphragm of the present invention has excellent heat resistance and electrolyte storage capacity, good structural stability, good ion conductivity, which is beneficial to improving the efficiency of battery cell injection and can improve the cycle performance of the battery.
[0025] (2) The method for preparing the composite diaphragm of the present invention comprises applying a mixed slurry formed by an inorganic filler, a polymer material and a solvent to at least one surface of a base film to obtain the composite diaphragm. The method can make the composite diaphragm have a specific composite coating and have excellent electrolyte storage capacity, structural stability and ion conductivity.
[0026] (3) The battery of the present invention has excellent cycle performance and high safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 is a schematic cross-sectional view of the composite diaphragm in Example 1 of the present invention; Figure 2 It is a schematic plan view of the composite coating of the composite membrane in Example 1 of the present invention; Figure 3 The secondary morphology of the composite coating of the composite membrane in Example 1 of the present invention; Figure 4 This is a schematic cross-sectional view of the composite diaphragm in Example 14 of the present invention.
[0029] Reference numerals: 1-base film, 2-composite coating, 201-convex structure, 202-concave structure. DETAILED DESCRIPTION
[0030] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0031] According to one aspect of the present invention, the present invention relates to a composite diaphragm, comprising a base film and a composite coating disposed on at least one surface of the base film; the composite coating comprises an inorganic filler and a polymer, and the polymer is selected from a first polymer, or a first polymer and a second polymer. The composite coating comprises a recessed portion and a raised portion; the raised portion comprises a plurality of parallel raised structures, the recessed portion comprises a plurality of parallel recessed structures, and the raised structures and the recessed structures are alternately distributed; the average thickness H2 of the recessed portion and the average thickness H1 of the raised portion satisfy: 0.2≤H2 / H1≤0.95; the average width W2 of the recessed portion and the average width W1 of the raised portion satisfy: 0.1≤W2 / W1≤9.
[0032] The composite diaphragm of the present invention has a composite coating of the above-mentioned specific structure. When the composite diaphragm and the pole piece are heat-set, the raised portion can effectively play the role of supporting space, and the recessed portion can effectively provide sufficient space to store electrolyte, which can provide a large amount of lithium ions for rapid charging and discharging; the continuous composite coating can effectively avoid the shrinkage problem of the composite diaphragm at high temperatures due to obvious uneven coating distribution; the composite diaphragm of the present invention has excellent heat resistance and electrolyte storage capacity, good structural stability, good ion conductivity, which is beneficial to improving the efficiency of battery cell injection and can improve the cycle performance of the battery.
[0033] In some embodiments, the ratio H2 / H1 of the average thickness H2 of the concave portion to the average thickness H1 of the convex portion is, for example, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.75, 0.8, 0.85, 0.9 or 0.95, or any range between the two. In some embodiments, the ratio W2 / W1 of the average width W2 of the concave portion to the average width W1 of the convex portion is, for example, 0.1, 0.2, 0.5, 0.8, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5 or 9, or any range between the two. The ratio of the average thickness H2 of the recessed portion to the average thickness H1 of the raised portion is within the above-mentioned appropriate range, and the ratio of the average width W2 of the recessed portion to the average width W1 of the raised portion is within the above-mentioned range, which is more conducive to coordinating and ensuring the supporting effect and liquid storage effect of the composite coating, and ensuring its heat resistance and electrical conductivity.
[0034] In some embodiments, the average thickness H1 of the convex structure is 0.5-15 μm, such as 0.5 μm, 1 μm, 1.5 μm, 2 μm, 3 μm, 5 μm, 6 μm, 8 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, etc., or any range between the two. The convex portion of the present invention has a suitable average thickness to ensure the above-mentioned effect of the composite coating and the overall performance of the composite diaphragm.
[0035] In some embodiments, the average width W1 of the convex structure is 0.1-10 mm, such as 0.1 mm, 0.5 mm, 0.8 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or 10 mm, or any range between the two. The convex structure of the present invention has a suitable average width, which is conducive to ensuring the support effect and improving the structural stability of the composite diaphragm.
[0036] In some embodiments, the average thickness H2 of the concave portion and the average thickness H1 of the convex portion satisfy: 0.55≤H2 / H1≤0.8. In some embodiments, the average width W2 of the concave portion and the average width W1 of the convex portion satisfy: 1≤W2 / W1≤3. Further preferred is the ratio range of the average thickness H2 to the average thickness H1 of the convex portion, and the ratio range of the average width W2 of the concave portion to the average width W1 of the convex portion, so as to ensure that the composite coating has better liquid retention, support, heat resistance and conductivity.
[0037] In some embodiments, the angle θ between the extension direction of the convex structure or the concave structure and the MD direction of the base film (longitudinal direction, i.e., the length direction of the base film) is 0 to 80°, for example, 0°, 10°, 20°, 30°, 40°, 45°, 50°, 60°, 70°, 80°, etc., or any range between the two. In some embodiments, the angle θ between the extension direction of the convex structure or the concave structure and the MD direction of the base film is 60° to 80°. The extension direction of the convex structure or the concave structure has a suitable angle with the MD direction of the base film, thereby ensuring the structural stability, liquid storage effect and heat resistance of the composite diaphragm.
[0038] In some embodiments, when the convex structure is observed from the spreading direction of the base film, the width error δ1 of the convex structure in the continuous extension dimension satisfies: δ1=(W1 max -W1 min ) / W1 min ≤10%, where W1 max Indicates the maximum width of the convex structure, W1 min represents the minimum width of the convex structure. The width error δ2 of the concave structure in the continuous extension dimension satisfies: δ2=(W2 max -W2 min ) / W2 min ≤10%, of which W2 max represents the maximum width of the concave structure, W2 min Represents the minimum width of the concave structure.
[0039] In some embodiments, in a cross section of the composite coating (the cross section is perpendicular to the length direction of the base film), the convex structures and the concave structures are in an arc-shaped sinusoidal wave configuration or a linear platform configuration.
[0040] In some embodiments, in the composite coating, the mass percentage of the inorganic filler is 67% to 97%, such as 67%, 70%, 75%, 80%, 85%, 90%, 95%, 97%, etc. The mass percentage of the second polymer is 0% to 30%, such as 1%, 2%, 4%, 5%, 6%, 10%, 15%, 18%, 20%, 25%, 30%, etc. When the polymer is selected from the first polymer and the second polymer, the mass percentage of the first polymer is 1% to 8%, such as 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, etc. In the composite coating of the present invention, the second polymer acts as a bonding layer during hot pressing of the composite diaphragm, and the first polymer can act as a bonding inorganic filler and base film. Each component has a suitable mass percentage and plays a role in coordination to ensure the bonding performance of the composite coating and the heat resistance, liquid storage performance and structural stability of the composite diaphragm.
[0041] In some embodiments, the inorganic filler includes at least one of alumina, boehmite, silica, magnesium hydroxide, barium sulfate, calcium carbonate, titanium dioxide, silicon carbide and silicon nitride, such as a combination of silica and magnesium hydroxide, a combination of calcium carbonate and titanium dioxide, a combination of titanium dioxide, silicon carbide and silicon nitride, etc. In some embodiments, the D50 particle size of the inorganic filler is 0.2 to 0.8 μm, such as 0.2 μm, 0.3 μm, 0.5 μm, 0.6 μm, 0.8 μm, etc.
[0042] In some embodiments, the second polymer includes at least one of polyvinylidene fluoride, polymethyl methacrylate, polyamide, polyimide and polyacrylonitrile, such as a combination of polyvinylidene fluoride and polymethyl methacrylate, and a combination of polyimide and polyacrylonitrile. In some embodiments, the particle size D50 of the second polymer is 7 to 12 μm, such as 7 μm, 8 μm, 9 μm, 10 μm, 11 μm or 12 μm, etc.
[0043] In some embodiments, the first polymer includes at least one of polyacrylate, polyurethane acrylate, styrene-butadiene rubber, polyvinyl alcohol and polyacrylamide, such as a combination of polyacrylate and polyurethane acrylate, a combination of polyvinyl alcohol and polyacrylamide, and the like.
[0044] In some embodiments, the base film comprises PP (polypropylene) and / or PE (polyethylene).
[0045] In some embodiments, the base film has a thickness of 2 to 20 μm, for example, 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 20 μm, etc.
[0046] In some embodiments, the thermal shrinkage rate of the composite membrane baked at 130° C. for 1 hour satisfies: the MD thermal shrinkage rate is 0.4% to 12.2%, such as 0.4%, 0.5%, 1%, 2%, 3%, 4%, 9%, 10%, etc., and the TD thermal shrinkage rate is 0.3% to 11.3%, such as 0.3%, 0.5%, 1%, 3%, 4%, 5%, 8%, 11%, etc. The composite membrane of the present invention has excellent thermal shrinkage performance.
[0047] In some embodiments, the electrolyte diffusion length of the composite membrane is 51-60 mm, such as 51 mm, 52 mm, 55 mm, 56 mm, 58 mm, 60 mm, etc. The composite membrane of the present invention is conducive to promoting the diffusion rate of the electrolyte.
[0048] According to another aspect of the present invention, the present invention also relates to a method for preparing the composite diaphragm as described above, comprising the following steps: The inorganic filler, the polymer material and the solvent are mixed to obtain a mixed slurry, the mixed slurry is coated on at least one side of the surface of the base film, and the composite diaphragm is obtained after drying.
[0049] The preparation method of the composite diaphragm of the present invention comprises applying a mixed slurry formed by an inorganic filler, a polymer material and a solvent to at least one surface of a base film to obtain the composite diaphragm. The method can make the composite diaphragm have a specific composite coating, and has excellent electrolyte storage capacity, structural stability and ion conductivity.
[0050] In some embodiments, the mass ratio of the inorganic filler to the solvent is (67-97): (122-400).
[0051] In some embodiments, the mass ratio of the inorganic filler, the second polymer, the first polymer and the solvent is (67-97): (1-30): (1-8): (122-400), such as 67:25:8:350, 70:25:5:330, 80:17:3:300, 90:6:4:300, 97:2:1:350, etc. The inorganic filler, the second polymer, the first polymer and the solvent of the present invention have a suitable mass ratio to ensure that the mixed slurry has a suitable concentration to ensure the coating effect.
[0052] In some embodiments, the coating of the present invention can be performed by roller coating. By setting the specifications (depth, angle) of the roller of the roller coating device and controlling the coating amount, the desired structure and size of the concave and convex parts of the composite coating can be obtained.
[0053] In some embodiments, the solvent includes water, such as deionized water.
[0054] According to another aspect of the present invention, the present invention also relates to a battery, comprising the composite separator.
[0055] The battery of the present invention has excellent cycle performance and high safety performance.
[0056] The battery of the present invention comprises the composite diaphragm, a positive electrode sheet, a negative electrode sheet and an electrolyte.
[0057] In some embodiments, taking a cylindrical battery cell as an example, the angle between the injection direction and the MD direction of the base film is 90°. In some embodiments, the angle between the direction of the convex structure or the concave structure and the injection direction is 0-30°.
[0058] In some embodiments, the injection time of the battery is 188-234 s, such as 188 s, 190 s, 192 s, 195 s, 200 s, 205 s, 210 s, 220 s, etc. The battery of the present invention can further reduce the injection time and improve the injection efficiency.
[0059] In some embodiments, the capacity retention rate of the battery after 300 cycles of charge and discharge at 0.3C is greater than or equal to 92%, such as 92% to 97%, such as 93%, 94%, 95%, 96%, 97%, etc. The battery of the present invention has a high capacity retention rate.
[0060] The following is further explained in conjunction with specific embodiments and comparative examples.
[0061] Example 1 A composite diaphragm includes a base film 1 and a composite coating 2 located on one side of the base film 1, wherein the composite coating 2 includes a concave portion and a convex portion; the convex portion includes a plurality of parallel convex structures 201, and the concave portion includes a plurality of parallel concave structures 202, wherein the convex structures 201 and the concave structures 202 are alternately distributed; the convex structure 201 has a thickness H1=2.0μm and a width W1=0.8mm, and the concave structure 202 has a thickness H2=1.4μm and a width W2=1.2mm; the angle θ between the concave-convex structure pattern and the MD direction of the base film 1 is 60°. The convex structure 201 and the concave structure 202 are in a sinusoidal wave configuration.
[0062] The cross-sectional schematic diagram of the composite diaphragm in this embodiment is shown in FIG. Figure 1 The plan view of the composite coating 2 of the composite membrane is shown in Figure 2 The secondary morphology of the composite coating 2 of the composite diaphragm is shown in Figure 3 shown.
[0063] The method for preparing the composite diaphragm of this embodiment comprises the following steps: Take 95 parts of alumina ceramic (D50=0.4μm) filler, add 330 parts of deionized water, stir evenly; then add 5 parts of polyacrylate and disperse fully. Use roller coating to coat the mixed slurry on one side of the PE-7μm base film 1, dry it, and obtain a composite diaphragm.
[0064] Example 2 A method for preparing a composite diaphragm, which differs from Example 1 in that: The angle θ between the concave-convex structure and the MD direction is 0°.
[0065] Example 3 A method for preparing a composite diaphragm, which differs from Example 1 in that: The angle θ between the concave-convex structure and the MD direction is 80°.
[0066] Example 4 A method for preparing a composite diaphragm, which differs from Example 1 in that: The thickness H2 of the concave structure 202 is adjusted to be 1.1 μm.
[0067] Example 5 A method for preparing a composite diaphragm, which differs from Example 1 in that: The thickness H2 of the concave structure 202 is adjusted to be 0.9 μm.
[0068] Example 6 A method for preparing a composite diaphragm, which differs from Example 1 in that: The thickness H2 of the concave structure 202 is adjusted to be 0.4 μm.
[0069] Example 7 A method for preparing a composite diaphragm, which differs from Example 1 in that: The thickness H2 of the concave structure 202 is adjusted to be 1.6 μm.
[0070] Example 8 A method for preparing a composite diaphragm, which differs from Example 1 in that: The thickness H2 of the concave structure 202 is adjusted to be 1.9 μm.
[0071] Example 9 A method for preparing a composite diaphragm, which differs from Example 1 in that: The width W2 of the concave structure 202 is adjusted to 0.8 mm.
[0072] Example 10 A method for preparing a composite diaphragm, which differs from Example 1 in that: The width W2 of the concave structure 202 is adjusted to 0.1 mm.
[0073] Embodiment 11 A method for preparing a composite diaphragm, which differs from Example 1 in that: The width W2 of the concave structure 202 is adjusted to 2.4 mm.
[0074] Example 12 A method for preparing a composite diaphragm, which differs from Example 1 in that: The width W2 of the concave structure 202 is adjusted to 7.2 mm.
[0075] Embodiment 13 A method for preparing a composite diaphragm, which differs from Example 1 in that: The convex structure 201 is adjusted to have a thickness of H1 = 0.5 μm and a width of W1 = 0.2 mm, and the concave structure 202 is adjusted to have a thickness of H2 = 0.4 μm and a width of W2 = 0.3 mm. At the same time, the same composite coating is applied to both sides of the base film 1 .
[0076] Embodiment 14 A composite diaphragm, such as Figure 4As shown, it includes a base film 1 and a composite coating 2 located on one side of the base film 1, the composite coating 2 includes a concave portion and a convex portion; the convex portion includes a plurality of parallel convex structures 201, the concave portion includes a plurality of parallel concave structures 202, the convex structures 201 and the concave structures 202 are alternately distributed; the convex structure 201 has a thickness H1=15.0μm and a width W1=10.0mm, the concave structure 202 has a thickness H2=9.0μm and a width W2=10.0mm; the angle between the concave-convex structure pattern and the MD direction is 60°. The convex structure 201 and the concave structure 202 are in a platform configuration.
[0077] The preparation method of the composite diaphragm comprises the following steps: Take 75 parts of alumina ceramic (D50=0.4μm) filler, add 350 parts of deionized water, stir evenly; then add 20 parts of PVDF (D50=9μm) and 5 parts of glue (polyurethane acrylate) components to fully disperse. Use roller coating to apply the mixed slurry on the substrate diaphragm and dry it to obtain a composite diaphragm.
[0078] Comparative Example 1 A method for preparing a composite diaphragm comprises the following steps: Take 95 parts of alumina ceramic (D50=0.4μm) filler, add deionized water, stir evenly; then add 5 parts of polyacrylate and disperse fully. Use roller coating to coat the mixed slurry on the substrate diaphragm, dry it, and obtain a composite diaphragm with a full coating thickness of 2.0μm.
[0079] Comparative Example 2 A method for preparing a composite diaphragm, which differs from Example 1 in that: The thickness H2 of the concave structure 202 is 0 μm.
[0080] Comparative Example 3 A method for preparing a composite diaphragm comprises the following steps: Take 10 parts of 45% solid content polyacrylate emulsion, 20 parts of thickener (CMC premixed aqueous solution), 80 parts of PVDF, stir at 25°C and 1000rpm for 1.5h; add 100 parts of DI water and mix, add 0.5 parts of fluoroalkyl methoxy alcohol ether, stir at 25°C and 500rpm / min for 60min to obtain polymer slurry (from CN115498360A).
[0081] The mixed slurry was coated on the substrate diaphragm by roller coating and dried to obtain a composite diaphragm with a full coating thickness of 2.0 μm. The mixed slurry was coated on the substrate diaphragm by roller coating and dried to obtain a composite diaphragm with a convex structure 201 having a thickness of H1=15.0 μm and a width of W1=10.0 mm, a concave structure 202 having a thickness of H2=9.0 μm and a width of W2=10.0 mm; and an angle of 60° between the concave-convex structure and the MD direction.
[0082] Experimental example 1. Performance test of composite diaphragm The composite diaphragms of the embodiments and comparative examples were tested for performance as follows: 1. Convex structure and concave structure thickness test: Using CP-SEM technology, 6 positions of each group of diaphragms are randomly sampled within the range of convex structure and concave structure, and the thickness of convex structure and concave structure are recorded and the average value is taken.
[0083] 2. Convex structure and concave structure width test: With the help of a two-dimensional image tester (JTVMA-3020), using the transmittance of light, the image of the convex structure is dark; the light transmittance of the concave structure is strong, and it appears bright white. Measure the width of the convex structure or concave structure along the direction perpendicular to the convex structure or concave structure (that is, the distance between the two adjacent dividing lines of the convex structure and the concave structure); randomly sample 6 positions for each group of diaphragms and take the average value.
[0084] 3. Angle test of convex structure and concave structure texture: Use a protractor to measure the angle between the convex structure and concave structure texture and the MD direction; randomly sample 6 positions for each group of diaphragms and take the average value.
[0085] 4. Composite diaphragm heat shrinkage test: The composite diaphragm was cut into 10cm×10cm (MD direction: length L×TD direction width W). Six samples were taken from each group of diaphragms and baked at 130℃ for 1h. The heat shrinkage rate of the diaphragm was recorded (MD=(Lbefore baking-Lafter baking) / Lbefore baking×100%; TD=(Wbefore baking-Wafter baking) / Wbefore baking×100%) and the average value was taken.
[0086] 5. Test of electrolyte diffusion rate on composite diaphragm coating: The composite diaphragm is cut into 5mm×200mm (MD: 5mm, TD: 200mm) along the TD direction, and 4 strips are cut from each group of diaphragms. 10μEC:EMC:DEC=3:5:2 lithium salt electrolyte is dripped on the center of the long strip diaphragm, and the diffusion time is 2min. The diffusion length is recorded and the average value is taken.
[0087] The performance test results of the composite membrane are shown in Table 1.
[0088] Table 1 Performance test results of composite diaphragm
[0089] 2. Battery performance test Injection time test: The composite diaphragm of each embodiment or comparative example is respectively wound with the lithium iron phosphate positive electrode sheet and the graphite negative electrode sheet to form a cylindrical lithium-ion battery. Six cells are prepared for each group of diaphragms, and the injection is carried out under the conditions of dew point -40°C and temperature 23°C. The total injection amount of lithium salt electrolyte EC:EMC:DEC=3:5:2 is 5g. The time used for each cell is recorded and the average value is taken.
[0090] Capacity retention rate: The composite diaphragm of each embodiment or comparative example was respectively wound with a lithium iron phosphate positive electrode sheet and a graphite negative electrode sheet to form a soft-package lithium-ion battery. The battery was cycled 300 times at 0.3C charge and discharge, and the capacity before and after the cycle was tested. Capacity retention rate = capacity after cycle / capacity before cycle.
[0091] The performance test results of the battery are shown in Table 2.
[0092] Table 2 Battery performance test results
[0093] It can be seen from Tables 1 and 2 that the composite membranes obtained by the method of the present invention have excellent heat resistance and suitable electrolyte diffusion performance. The injection time of the batteries obtained by each composite membrane can be shortened, and the capacity retention rate is relatively high, at more than 92%.
[0094] By comparing Example 1, Example 4, Example 5, Example 6 and Comparative Example 2, the more the ratio of the concave structure thickness H2 to the convex structure thickness H1 deviates from 100%, the more severe the heat shrinkage is. In Comparative Example 2, H2 / H1=0, the heat shrinkage is significantly aggravated, the MD heat shrinkage is 15.4%, and the TD heat shrinkage is 14.1%.
[0095] Comparing Examples 1 to 13 and Comparative Example 1, there is no significant difference in the electrolyte diffusion length, indicating that the coating structure has a small effect on the electrolyte diffusion rate. Comparing Example 1 with Comparative Example 2, the diffusion length of Example 1 is much greater than that of Comparative Example 2, indicating that the discontinuous coating greatly weakens the electrolyte diffusion rate. Comparing Example 14 with Comparative Example 3, the diffusion length of Example 14 is much greater than that of Comparative Example 3, indicating that the alumina-containing ceramic coating greatly promotes the electrolyte diffusion rate.
[0096] Comparing Example 1, Example 2 and Example 3, the closer the MD angle between the concave structure or the convex structure and the substrate is to 90°, the shorter the required injection time is.
[0097] Comparing Example 1, Example 4, Example 5, Example 7, Example 8, Comparative Example 1 and Comparative Example 2, the closer the ratio of the concave structure thickness H2 to the convex structure thickness H1 is to 0%, the higher the capacity retention rate is; when H2 / H1 decreases from 80%, the capacity retention rate increases but not significantly; but when H2 / H1 is 0%, the capacity retention rate decreases significantly, indicating that a certain thickness of coating is required at the concave structure.
[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite diaphragm, characterized in that: It comprises a base film and a composite coating disposed on at least one side of the base film; the composite coating comprises an inorganic filler and a polymer material, and the polymer material is selected from a first polymer, or a first polymer and a second polymer; The composite coating comprises a concave portion and a convex portion; the convex portion comprises a plurality of parallel convex structures, the concave portion comprises a plurality of parallel concave structures, and the convex structures and the concave structures are alternately distributed; The average thickness H2 of the concave portion and the average thickness H1 of the convex portion satisfy: 0.2≤H2 / H1≤0.95; The average width W2 of the concave portion and the average width W1 of the convex portion satisfy: 0.1≤W2 / W1≤6.5; the average width W1 of the convex structure is 0.8~10mm; The first polymer includes at least one of polyacrylate, polyurethane acrylate, styrene-butadiene rubber, polyvinyl alcohol and polyacrylamide; The second polymer includes at least one of polyvinylidene fluoride, polymethyl methacrylate, polyamide, polyimide and polyacrylonitrile.
2. The composite diaphragm according to claim 1, characterized in that: Contains at least one of the following features (1) to (3): (1) The average thickness H1 of the convex structure is 0.5-15 μm; (2) The average thickness H2 of the concave portion and the average thickness H1 of the convex portion satisfy: 0.55≤H2 / H1≤0.8; (3) The average width W2 of the concave portion and the average width W1 of the convex portion satisfy: 1≤W2 / W1≤3.
3. The composite diaphragm according to claim 1, characterized in that: An angle θ between an extending direction of the convex structure or the concave structure and an MD direction of the base film is 0-80°.
4. The composite diaphragm according to claim 3, characterized in that: An included angle θ between an extending direction of the convex structure or the concave structure and an MD direction of the base film is 60° to 80°.
5. The composite diaphragm according to claim 1, characterized in that: Contains at least one of the following features (1) to (3): (1) The width error δ1 of the convex structure in the continuous extension dimension satisfies: δ1=(W1 max -W1 min ) / W1 min ≤10%, where W1 max Indicates the maximum width of the convex structure, W1 min Indicates the minimum width of the convex structure; (2) The width error δ2 of the concave structure in the continuous extension dimension satisfies: δ2=(W2 max -W2 min ) / W2 min ≤10%, of which W2 max represents the maximum width of the concave structure, W2 min represents the minimum width of the concave structure; (3) In the cross section of the composite coating, the convex structure and the concave structure are in an arc-shaped sinusoidal wave configuration or a linear platform configuration.
6. The composite diaphragm according to claim 1, characterized in that: Contains at least one of the following features (1) to (2): (1) In the composite coating, the mass percentage of the inorganic filler is 67% to 97%, and the mass percentage of the second polymer is 0% to 30%; (2) The inorganic filler includes at least one of alumina, boehmite, silicon dioxide, magnesium hydroxide, barium sulfate, calcium carbonate, titanium dioxide, silicon carbide and silicon nitride.
7. The composite diaphragm according to claim 1, characterized in that: Contains at least one of the following features (1) to (2): (1) The base film comprises PP and / or PE; (2) The thickness of the base film is 2 to 20 μm.
8. The method for preparing a composite diaphragm according to any one of claims 1 to 7, characterized in that: The following steps are involved: Mixing an inorganic filler, a polymer material and a solvent to obtain a mixed slurry; The mixed slurry is coated on at least one side of the surface of the base film, and the composite diaphragm is obtained after drying.
9. The method for preparing a composite diaphragm according to claim 8, characterized in that: The mass ratio of the inorganic filler to the solvent is (67-97):(122-400).
10. A battery, characterized in that: A composite diaphragm comprising any one of claims 1 to 7.
Citation Information
Patent Citations
Twill polymer composite diaphragm as well as preparation method and application thereof
CN115498360A
Composite lithium battery separator and preparation method therefor
CN110859053A
Composite diaphragm as well as preparation method and application thereof
CN113178663A
Battery diaphragm and preparation method thereof, battery and electronic device
CN117438743A
Secondary battery and electric device
WO2024113988A1
Cited By
Coated diaphragm as well as preparation method and application thereof
CN120999257A
A coated separator, its preparation method and use
CN120999257B